SP0012 How To Assess The CVD Risk in The Individual Patient?. (15th July 2016) - Sattar, N.
Abstract : This talk will overview the methods of assessing CVD risk in patients with Rheumatoid arthritis. It will give a rationale for why CVD risk screening in RA can be done using risk scores developed for the general population and also give two examples of scores which include RA as a risk stratifier. The talk will highlight that i) CVD risk scoring is easy to do in routine clinical practice, ii) requires simple additional of non-fasting lipids and blood pressure, iii) can be intergrated to existing RA clinics and iv) can be repeated at intervals of time which is pragmatic. The talk will further emphasise that consideration of usual CVD risk factors is critically important in determing who should be recommended statins and that having RA alone does not mean individuals are necessarily at high CVD risk. A case history will be used to highlight main points discussed in the talk. Finally, the talk will also discuss the pros and cons of additional tests and discuss the recommendations from recent guidelines which will fit in with the talks conclusions. Disclosure of Interest: N. Sattar Consultant for: Roche, Astrazeneca, Amgen, Sanofi, Merck, Speakers bureau: Roche